Attack of the bullies - Buckley, Michael, 1969- (NERDS, 2013)
When Ms. Information kidnaps the President's daughter, it is up to twelve-year-old Ruby, also known as Pufferfish, to use her super-nanobyte-enhanced allergies in leading the NERDS' investigation.